(3TQM ebGeGJ GdMQjQjs - (3eXgQ GdOjf GdTjQGRis; (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi JdCdCJ ThGgO bOQJg Ydi hLfGJ GdehLhOGJ s
(3BNQgG (B:s
(3hCgd GdJbhi jYfi gh Cgd Cf jJbi Gi jMPQ hjLJfH YUjGfg jYfi gh eYWi dgG NjQ ai GdOfjG hGdBNQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B536s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs